Identification of the Patterns Produced in the Offensive Sequences That End in a Goal in European Futsal - Amatria, Mario; Álvarez, Javier; Ramírez, Javier; Murillo, Víctor (Frontiers in Psychology, 2021)
Victory is the ultimate aim in high performance sports; when it comes to team sports, the goal is the key that allows players to achieve that victory. This is the case with futsal which, due to its internal structure as well as the speed in the development of its game, makes the achievement of a goal not an isolated event, but rather more than one goal must be scored to achieve victory. The aim of the present study is to analyze the construction of offensive sequences that have resulted in goal-scoring in the two main European futsal leagues, the Spanish and the Italian, as well as to identify the patterns relating to offensive actions that have ended with a goal being scored. Observational methodology was used to develop the research and an ad hoc observation instrument (OAF-I) was developed for this purpose. The data was analyzed using inferential statistics as well as sequential analysis of delays in a diachronic analysis to identify the patterns of offensive actions. The results obtained enable recognition of a league’s idiosyncrasy patterns in goal-scoring in each of the leagues studied. The results obtained will allow experts to have a better understanding of how goals are scored and how to establish more specific training tasks, in both attack and defense.